The Influence of the Activation Temperature on the Structural Properties of the Activated Carbon Xerogels and Their Electrochemical Performance - Nguyen Khanh Nguyen Quach; Wein-Duo Yang; Zen-Ja Chung; Hoai Lam Tran (Advances in Materials Science and Engineering)
The effect of activation temperature on the structural properties and the electrochemical performance of KOH-activated carbon xerogel was investigated in range of 700 to 1000°C. At a high temperature (1000°C), the chemical activation regenerated a more crystalline network structure of activated carbon xerogels, which was observed by Raman, XRD, and TEM images. Additionally, SEM images, BET, BJH, and t-plot were used to study the structural properties of carbon xerogels. The carbon xerogel sample activated at 900°C was found with the most appropriate structure, which has the high micropore area and a more-balanced porosity between the micropores and mesopores, for using as an electrode material. The highest obtained specific capacitance value was 270 Fg−1 in 6 M KOH electrolyte at scan rate of 5 mVs−1 from the cyclic voltammetry.